The Oxford movement and its leaders: a bibliography of secondary and lesser primary sources - Crumb, Lawrence N. (ATLA bibliography series, 2009)
.cs2654AE3A{text-align:left;text-indent:0pt;margin:0pt 0pt 0pt 0pt}.csC98BA9AD{color:#000000;background-color:transparent;font-family:Times New Roman; font-size:12pt; font-weight:normal; font-style:italic; }.cs566403DE{color:#000000;background-color:transparent;font-family:Times New Roman; font-size:12pt; font-weight:normal; font-style:normal; }The Oxford Movement and Its Leaders is a comprehensive bibliography of books, pamphlets, chapters in books, periodical articles, manuscripts, microforms, and tape recordings dealing with the Movement and its influence on art, literature, and music, as w